(untitled) (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2025)
Tasks play a pivotal role regarding cognitive activation in language-sensitive subject matter lessons. This article presents a comprehensive discussion of quality criteria for tasks in that context drawn from a multitude of interdisciplinary perspectives. It offers a multidimensional grid for the analysis and design of task formats, which can assist (prospective) teachers in developing language-sensitive cognitively activating tasks – even in the absence of prior knowledge of applied linguistics.